How to Optimism Affects The Work Family Balance of Church Full-timmer - Yonathan Setyawan; Triana Noor Edwina Soeharto (Psycho Holistic, 2021)
This study aims to determine the relationship between optimism and work family balance of fulltimer on Christian church. The subjects in this study were 75 full-timers on Christian churches in the former residency of Madiun with predetermined criteria. The data collection tool used is the work family balance scale and the optimism scale. The analysis technique uses the product moment correlation and regression technique to analyze. The results of the analysis show that there is a positive relationship between optimism and work family balance in church fulltimers with a correlation value of 0.580 (p<0.01). The amount of effective contribution of optimism with work family balance is 28.3%, and the remaining 71.7% is influenced by other variables. The Work Family Balance category for church fulltimers is in the medium category, which is 93.3% and the Optimism of church fulltimers is in the medium category, which is 76%.